Relevansi Akulturasi Tradisi Weton Terhadap Strategi Konstruksi Pendidikan Islam - Muhamad Takrip; Dafis Heriansyah (Indonesian Journal of Islamic Educational Review, 2024)
Acculturation of culture and tradition is a necessity for the substance of Islamic education in the era of globalization, sensitive to the development of information and communication technology, requiring a strategy for constructing a process of instilling a mindset that is able to explore knowledge. So that it will produce actions that are in accordance with the potential possessed by humans in solving problems, making decisions, and learning new concepts such as the weton tradition. This is a combination of the day and market when a baby is born into the world which is still used by most people in determining a good day when they are going to get married, to build a house, move house or to determine the time of circumcision. Islamic education is essentially a process of socialization with the environment. This research is an ethnographic research which is one approach in qualitative research methods that seeks to explore a community culture. The results of the study concluded that the relevance of acculturation of the weton tradition can be implemented by fostering character in developing traditions into the realm of Islamic education in the era of globalization by reconstructing the components of Islamic education in making decisions to learn new concepts with the principle of taking the goodness of old traditions, developing and taking new traditions that are better,